Kekuatan perlekatan geser semen ionomer kaca terhadap dentin dan NiCr alloy (Shear bond strenght of glass ionomer cement in dentin and NiCr alloy) - Mira Leonita; R. Iskandar (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2005)
Glass ionomer cements were used broadly in restorative dentistry. That’s why researchers always try to invent new form of glass ionomer cement. The newest invention was the paste-paste formulation. Shear bond strenght of powder-liquid glass ionomer cement and paste-paste glass ionomer cement in dentin and NiCr alloy was tested to 4 groups of samples. Each group consisted contain 6 samples that were shaped into cylinder with 4 mm of diameter and 5 mm of height. Group A was dentin with powder-liquid glass ionomer cement, group B was dentin with paste-paste glass ionomer cement, group C was alloy with powder-liquid glass ionomer cement, and group D was alloy with paste-paste glass ionomer cement. Each sample in each group was tested with Autograph. The datas were analyzed statistically using T-test with level of signficance 0.05. The result showed that powder-liquid glass ionomer cement shear bond strenght was 211 N and paste-paste glass ionomer cement was 166.92 N. That showed that powder-liquid glass ionomer cement had a better shear bond strenght.